(3OjhGf GdCYSes - (3YHGS GdGYSes ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3agPG OjhGf GdaGVd GdTjN YHGS GdCYSe oLeYJ ef ChQGb HNWg, hQJHJg Ydi GdMQha hoCdMbJ HBNQg GdJNGejS s
(3BNQgG (B:s
(3hEffj YfOeG bO SQge Cdej bO SQfj Cfge bO SQge Sbej aGROOJ cjeG jSQhG aj Gdghi SbeG s
(3ocJHJ YfGhjf HYV GdbUGFO HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B28 s
Keywords: (3GdCOHs